Do integrative approaches to health contribute to self-reliance in primary healthcare? reflections from a community case study in Kerala, India - BS Shivanand; M Tushara; PM Unnikrishnan; Jayanna Krishnamurthy (Health Psychology and Behavioral Medicine, 2022)
A pluralistic Health system provides options for people to choose appropriate healthcare approach. However, the ability to make informed decision is infleuenced by many factors. An informed decision is one of the attributes of self-reliance. In this study, through the interactions with smallholder farmers, we tried to travel through the realm of communities’ integrative practices and perceptions with a specific focus on traditional medicine concerning animal and human health. We aimed to understand what influences healthcare choices, mainly traditional medicine among people and how it contributes to self-reliance in primary healthcare. We conducted this case study in Aluva taluk of Ernakulam district in Kerala, India. Study participants were selected using the purposive sampling method and the data collected through 22 in-depth interviews and participant observation.Integrative healthcare practice is fragmented due to variations in the evidence perception by the people. Personal experiences, social and cultural factors, and health literacy influence health decisions in practicing integrative healthcare. Therefore, while investigating a concept like self-reliance, there is a need for analytical methods to embrace experiential, textual, inherited, and incorporated forms of learning. This further helps researchers and policymakers to recommend context-specific and sustainable solutions to create self-reliant communities in primary healthcare.